OBRA SIMBÓLICA DO BRASIL NOVO: REPRESENTAÇÕES FOTOGRÁFICAS DE GETÚLIO VARGAS NA “TERRA DOS PINHEIRAIS” EM 1944 - Santos, Jessica Leme (2017)
The New State, that includes the years of (1937-1945), was known as the longest period of influence of varguist political propaganda. With the creation of DIP – Departamento de Imprensa e Propaganda (Department of Press and Propaganda), the divulgation and impression of Getúlio Vargas image has been systemized. About this, this research has as objective to analyze the photographical images of President Getúlio Vargas during his visit in Paraná state in 1944. These photographical images are inserted in a Commemorative Album of Visit of President Vargas, 1944, a material used as politic propaganda. Also, it sought to analyze the discourses during the publication, which has approached various themes as the 1930 Revolution, Paranism, Paraná industrialization in the 30’s and 40’s, as well government aspects, for example, immigration/reoccupation of Paraná’s north, the eugenic theory, etc. To analyze the images, it applies the using of iconography/iconology, intending to dismount the photographic sign. To discuss about Vargas representation, it uses the representation concepts of Chartier, where intends to understand the mechanisms used to construct the president’s image.